The Existence of Cartooning Education in Semarang City - Prehanto, Adi; Aprily, Nuraly Masum (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
In particular, this research aimed to understand the educational portrait and training of cartoon art in the city of Semarang. Cartoon was part of a creative space that facilitates individuals who have an interest in cartoon creations. The existence of cartoon class in Indonesia is still not popular still like in Turkey, Iran, and Belgium. However, the Indonesian Gold Pencil Foundation is a space of cartoon artist in Indonesia, especially in Semarang city. This method applied of research qualitative. Research instruments included structured interview guidelines, deep observations, and documentation. The results of this study comprised the development of cartoon education in Semarang City is becoming new phenomenon, especially for students in elementary education, junior high school, and senior high school. The cartoon education in the city of Semarang was as a unique interest for some students, because it was able to develop their creativity and interest in animation. Abstrak Penelitian ini bertujuan untuk memahami potret edukasi dan pelatihan seni kartun di Kota Semarang. Seni menggambar kartun merupakan bagian dari ruang kreatif dalam memfasilitasi individu yang memiliki minat pada kreasi kartun. Keberadaan kelas kartun di Indonesia masih belum populer masih seperti di Negara Turki, Iran, dan Belgia. Namun, Yayasan Pensil Emas Indonesia merupakan ruang bagi seniman kartun di Indonesia, khususnya di Kota Semarang. Metode penelitian adalah kualitatif deskriptif. Instrumen penelitian mencakup pedoman wawancara terstruktur, pengamatan mendalam, dan dokumentasi. Hasil penelitian ini adalah gambaran komprehensif pendidikan menggambar kartun di Kota Semarang, terutama bagi siswa di bidang pendidikan dasar, SMP, dan SMA. Pendidikan kartun di Kota Semarang ini sebagai minat unik bagi sebagian siswa, karena mampu mengembangkan kreativitas dan minat mereka terhadap animasi.